Implant survival following primary total hip arthroplasty : With special interest in uncemented acetabular components and liners - Hemmilä, Matias (fi=Turun yliopisto|en=University of Turku|, 2021)
Total hip arthroplasty (THA) isregarded as the operation of the century. A successful THA is a combination of adequate surgical technique with appropriate implants performed for carefully selected patients. Orthopedic devices are undergoing continual development towards longer survival and better outcomes. However, development is demanding and time-consuming, because complications can become apparent years after a successful THA. Arthroplasty registers allow us to analyze the survival of implants in large volumes of patients, detect outlier implants, and avoid complications. This study is based on the Finnish Arthroplasty register. The aims of this thesis were: 1) to compare implant survival and revision risk of a Continuum cup (ZimmerBiomet, Warsaw, USA) with other uncemented cup devices in primary THA; 2) assess the survivorship of ultraporous Tritanium cups (Mahwah, NJ, USA) compared to conventional uncemented cups in primary THA; 3) evaluate revision rates between vitamin E-infused polyethylene liners and moderately crosslinked polyethylene (ModXLPE) liners from the same manufacturer in primary THA; and 4) describe a case report of trunnion corrosion and component failure and clarify risk factors based on the current literature. We found the Continuum cup component to be associated with an increased risk of revision compared to other uncemented cups in primary THA, mainly due to revisions for dislocation. The risk of dislocation decreased when an elevated liner was used with the Continuum cup. The ultraporous-coated Tritanium cup component for primary THA did not provide an advantage over traditional uncemented cups and was associated with increased revision risk for aseptic loosening of the cup. Vitamin E-infused liners are a durable option; however, we were unable to detect any advantages of this material associated with decreased wear, and further studies with longer follow-up are needed. Mechanically assisted crevice corrosion of the trunnion is a multifactorial phenomenon. Affecting factors can be divided into patient-related, component-related, and surgery-related. Severe trunnion corrosion due to mechanically assisted crevice corrosion (MACC) is a rare complication.

Lonkan tekonivelen kuppikomponentit ja liukupinnat ensivaiheen tekonivelleikkauksessa – tarkastelussa sementittömät kupit ja muoviliukupinnat Lonkan tekonivelleikkausta on pidetty yhtenä vuosisadan lääketieteellisistä toimenpiteistä. Oikea leikkaustekniikka yhdistettynä tarkoituksenmukaisiin tekonivelkomponentteihin tarkkaan valituilla potilailla on menestyksen edellytys. Tekoniveliin kehitetään jatkuvasti uusia ratkaisuja, joilla pyritään vähentämään komplikaatioita ja pidentämään tekonivelten elinkaarta, mutta kehitystyö on haastavaa ja aikaa vievää. Tämän tutkimuksen tarkoituksena oli analysoida lonkan tekonivelinnovaatioiden toimivuutta ja tuloksia. Erityisenä mielenkiinnon kohteena olivat sementittömät kuppikomponentit ja niissä käytettävät polyeteenistä valmistetut liukupinnat. Aineisto kerättiin Suomen Tekonivelrekisteristä. Vertasimme lonkan tekonivelen tantaalimetallisten Continuum -kuppikomponenttien sijoiltaanmenon ilmaantuvuutta suhteessa muihin yleisesti käytettyihin sementittömiin kuppikomponentteihin. Tutkimme titaanisen Tritanium kuppikomponentin uusintaleikkausmääriä suhteessa muihin sementittömiin primaari kuppikomponentteihin. Selvitimme lonkan tekonivelen E-vitamiinia sisältävän liukupinnan vaikutusta lonkkamaljan muoviliukupintaisten tekonivelten pysyvyyteen ja uusintaleikkausten syihin. Lisäksi raportoimme tapausselostuksen tekonivelen kartioliitoksen korroosiosta ja tekonivelen rikkoutumisesta ja sen riskitekijöistä kirjallisuuden ja oman tapauksemme perusteella. Tutkimuksessamme Continuum-kupeilla todettiin suurentunut riski uusintaleikkaukseen sijoiltaanmenon vuoksi. Korotettu liukupinta kuitenkin vähensi sijoiltaanmenon riskiä ja sen käyttö on suositeltavaa Continuum kuppia käytettäessä. Tritanium -kuppeihin liittyi tilastollisesti merkittävästi suurentunut uusintaleikkausriski kupin irtoamisen vuoksi. E-vitamiinia sisältävä polyeteeni liukupinta on kestävä valinta lonkan tekonivelleikkauksessa, mutta sen potentiaaliset edut eivät tulleet esiin 7 vuoden seuranta-aikana. Kartioliitoksen korroosio on monitekijäinen ilmiö, jonka riskitekijät voidaan jakaa potilaskohtaisiin, komponenttikohtaisiin ja toimenpidekohtaisiin.